Ontologi Sistem Penilaian E-Learning Berbasis Kompetensi - Desi Windisari; Sri Suning Kusumawardani; P. Insap Santosa (Forum Teknik, 2011)
Automation grading on e-Learning assessment helps educators in assessing the results of the exam. In a previous research, automation grading vaue jus in the form of numbers, not performed a review the achievement of competency standards. In this research we developed assessment system ontology design fo e-learning base competence. This propose ontology design models the relation between matter and competence then made the rule for the calculation of achievement students against each competency and make recommendations to the student passing the exam. From the test results with the protege show that ontology design can grade the assessment and give recommendations to the student passing the exam, in accordance with the rules made.Keywords : Ontology, assessment e-Learning, Automation grading.